2020
DOI: 10.3390/s20174821
|View full text |Cite
|
Sign up to set email alerts
|

Human-Like Obstacle Avoidance Trajectory Planning and Tracking Model for Autonomous Vehicles That Considers the Driver’s Operation Characteristics

Abstract: Developing a human-like autonomous driving system has gained increasing amounts of attention from both technology companies and academic institutions, as it can improve the interpretability and acceptance of the autonomous system. Planning a safe and human-like obstacle avoidance trajectory is one of the critical issues for the development of autonomous vehicles (AVs). However, when designing automatic obstacle avoidance systems, few studies have focused on the obstacle avoidance characteristics of human drive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…The development of human-like autonomous driving systems has in recent times gained increased attention from both technology companies and academic institutions alike, as it has the potential to improve the interpretability and acceptance of autonomous vehicle systems. [ 9 ] addressed the research gap found in the planning of a safe and human-like obstacle avoidance trajectory, which is one of the critical issues for the development of autonomous vehicles (AVs). The paper proposed an automatic obstacle avoidance system that focused on the obstacle avoidance characteristics of human drivers.…”
Section: Autonomy and Path Planningmentioning
confidence: 99%
“…The development of human-like autonomous driving systems has in recent times gained increased attention from both technology companies and academic institutions alike, as it has the potential to improve the interpretability and acceptance of autonomous vehicle systems. [ 9 ] addressed the research gap found in the planning of a safe and human-like obstacle avoidance trajectory, which is one of the critical issues for the development of autonomous vehicles (AVs). The paper proposed an automatic obstacle avoidance system that focused on the obstacle avoidance characteristics of human drivers.…”
Section: Autonomy and Path Planningmentioning
confidence: 99%
“…The development of human-like autonomous driving systems has in recent times gained increased attention from both technology companies and academic institutions alike, as it has the potential to improve the interpretability and acceptance of autonomous vehicle systems. [9] addressed the research gap found in the planning of a safe and humanlike obstacle avoidance trajectory, which is one of the critical issues for the development of autonomous vehicles (AVs). The paper proposed an automatic obstacle avoidance system that focused on the obstacle avoidance characteristics of human drivers.…”
Section: Autonomy and Path Planningmentioning
confidence: 99%
“…The optimal control problem for each sampling time is converted into a quadratic programming problem, while the MPC controller can effectively reduce the tracking error and ensure the stability of the vehicle. Sun [ 37 ] proposed a human-like trajectory planning and tracking model based on a model predictive control algorithm, and which considers the drivers’ operational characteristics. Liu J [ 38 ] considered the tracking effect and steering stability simultaneously, based on a three-degree-of-freedom nonlinear vehicle model.…”
Section: Introductionmentioning
confidence: 99%